2022
DOI: 10.1007/s00431-022-04390-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated multisystemic inflammatory syndrome in 614 children with and without overlap with Kawasaki disease-Turk MIS-C study group

Abstract: Multisystemic inflammatory syndrome (MIS-C) diagnosis remains difficult because the clinical features overlap with Kawasaki disease (KD). The study aims to highlight the clinical and laboratory features and outcomes of patients with MISC whose clinical manifestations overlap with or without KD. This study is a retrospective analysis of a case series designed for patients aged 1 month to 18 years in 28 hospitals between November 1, 2020, and June 9, 2021. Patient demographics, complaints, laboratory results, ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 17 publications
(21 reference statements)
5
36
0
Order By: Relevance
“…In addition, they found that the need for intensive care and shock development were more common in patients who did not overlap with KD. 32 In our study, there was an increase in inflammatory indicators including CRP, procalcitonin, ESR, ferritin, IL-6, and fibrinogen consistent with larger sample size studies. 16,23 In addition, thrombocytopenia, hypoalbuminemia, and high D-dimer levels were detected in the studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, they found that the need for intensive care and shock development were more common in patients who did not overlap with KD. 32 In our study, there was an increase in inflammatory indicators including CRP, procalcitonin, ESR, ferritin, IL-6, and fibrinogen consistent with larger sample size studies. 16,23 In addition, thrombocytopenia, hypoalbuminemia, and high D-dimer levels were detected in the studies.…”
Section: Discussionsupporting
confidence: 89%
“…Ciftdogan et al evaluated 614 patients with MIS-C. 32 The researchers classified patients according to whether or not they had clinical findings overlapping with KD, and compared laboratory findings in the two groups. In this study, 45.1% of patients with MIS-C had manifestations that overlapped with KD.…”
Section: Discussionmentioning
confidence: 99%
“…(Bowles et al, 2020) Recent reports on MIS-C after SARS-CoV-2 infection have also shown a frequent overlap of its clinical features with Kawasaki disease and other viral-associated hyperinflammatory syndromes, making an accurate diagnosis challenging. (Yilmaz Ciftdogan et al, 2022) Pathogenesis of Kawasaki-like MIS-C is thought to be immune complex-mediated, which derives in activation of inflammatory cells (including monocytes and neutrophils) and recruitment of platelets, resulting in thrombocytosis (commonly seen in Kawasaki disease and presented in our patient). (Lo & Newburger, 2018) Although there are several studies aiming to describe the pathophysiology and clinical characteristics of this condition, reports including specific recommendations for patients with MIS-C who also have surgical indications are mainly null.…”
mentioning
confidence: 79%
“…This lack of clarity is reflected in our study, where providers were divided when asked about the duration of fever that would prompt them to initiate workup. Additional thought also must be put into excluding other febrile illnesses, such as viral illnesses, bacterial infections, or Kawasaki disease, which can be particularly challenging given the overlapping clinical features [ 11 ].…”
Section: Discussionmentioning
confidence: 99%